Suggestibility in Kindergarteners and its relation to some variables - استبرق داود سلمان (College of Education for Women, 2019)
The childhood of the most important stages throughout the human and which have been more vulnerable to various factors surrounding it and with the scientific and cognitive development in all fields surfaced many psychological phenomena that play a large role in influencing children and their behavior trends is the susceptibility of the lure of psychological phenomena which plays a major role in the social attitudes of individuals it may not be predictable so that individuals vary in between them in terms of vulnerability Balasthoa You do this only _bl that the same individual at different influenced Balasthoa different depending on the positions and this was research to achieve its objectives and that are known: _ alasthoa The children Riyadh _ alfruq Statistically significant variable in Alasthoa depending on the sex of the child _ alfruq Statistically significant variable in Alasthoa depending on the order of the child in the family _ alfruq Statistically significant variable in Alasthoa depending on the educational attainment of the mother _ alfruq Statistically significant variable in Alasthoa depending on the attainment of the Lab The limited research on mothers of kindergarten children who are in kindergarten in the city of Baghdad, for the academic year 2014_2015 In order to achieve the objectives ofresearch, the researcher to adopt a measure (Mamouri 0.2011) The number of paragraphs of the scale "28" clause as well as a researcher statistical analysis of the vertebrae by the expense of discriminatory power, showing that paragraphs all distinct and statistically significant as well as find a relationship degrees paragraph mainly college was to make sure the stability of the scale in a way re-test, reaching reliability coefficient (0.86), and this shows that stability is good coefficient increased to apply Alvakronbach equation and found that the stability coefficient (0.83) and this shows that D. morally. The dish scale on a total sample number "200" from the mothers of the children Riyadh and research found to a number of conclusions, including the kindergarten children do not have the lure and there is a difference in Alasthoa between males and females variable in favor of females and then made a researcher a set of recommendations and proposals in the light of the search results.